2015
DOI: 10.1021/acs.langmuir.5b00812
|View full text |Cite
|
Sign up to set email alerts
|

Adlayer-Mediated Antibody Immobilization to Stainless Steel for Potential Application to Endothelial Progenitor Cell Capture

Abstract: This work describes the straightforward surface modification of 316L stainless steel with BTS, S-(11-trichlorosilylundecanyl)-benzenethiosulfonate, a thiol-reactive trichlorosilane cross-linker molecule designed to form intermediary coatings with subsequent biofunctionalization capability. The strategy is more specifically exemplified with the immobilization of intact antibodies and their Fab' fragments. Both surface derivatization steps are thoroughly characterized by means of X-ray photoelectron spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…(VEcadherin is a key adhesion molecule on the surface of endothelial cells that is a component of endothelial cell-to-cell adherens junctions, and also plays a key role in the maintenance of vascular integrity [31,32]). In this work, we show that BTS-modified medical grade steel offers the possibility to attach both intact antibodies and Fab' fragments to the substrate surface in a highly robust fashion as discussed previously [30]. This system displays enhanced stability and continued capability to bind antigenic species even following harsh rinsing conditions.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…(VEcadherin is a key adhesion molecule on the surface of endothelial cells that is a component of endothelial cell-to-cell adherens junctions, and also plays a key role in the maintenance of vascular integrity [31,32]). In this work, we show that BTS-modified medical grade steel offers the possibility to attach both intact antibodies and Fab' fragments to the substrate surface in a highly robust fashion as discussed previously [30]. This system displays enhanced stability and continued capability to bind antigenic species even following harsh rinsing conditions.…”
Section: Discussionmentioning
confidence: 53%
“…This surface linker is able to bind to any surface containing surface hydroxyl groups, and therefore can coat a variety of substrates including metals and polymers. We have shown that such a system was able to bind a target antigen specifically, which behaves as a proofof-concept model for stents [30]. Herein we demonstrate that this biologically active protocol is successful in the capture of endothelial cells and surface re-endothelialization.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…An antibody against vascular endothelial-cadherin has also been proposed to accelerate endothelial recovery and reduce neointimal formation on stainless steel stents compared with CD34-capture stents, [162] while endoglin/CD105, a type III accessory receptor for the transforming growth factor (TGF)-β superfamily, has also been identified as a potential cell marker, [163] and stainless steel stents coated with anti-endoglin immunoglobulins have been reported to perform as well as the Genous™ stent in porcine studies. [164] The enormous interest in EC and particularly EPC capture has also seen Fab′ fragments [131b] used to coat stent-like surfaces, [165] as well as circular RGD peptide [166] and DNA aptamers. [167] In all cases, however, the problem remains of ensuring only the target cell types and not other circulating cells are captured on the material by the surface-displayed biomolecule.…”
Section: Surface Coating For In Vivo Applicationsmentioning
confidence: 99%